Softwarové modely hudebních forem a tvůrčí proces jako metoda poznávání - Haas, Petr (Aura musica, 2025)
The study of musical forms can be supported by creative activity, which is close in nature to composing and uses play as an educational principle. Interactive dialogue with software models of musical forms offers such possibilities. The user inserts musical material into them and the model then automatically simulates the formation of a musical composition. This is based on the experience of so-called  ́computer- assisted composition ́, whose methods have been common in the field of classical music since the 1960s.
Keywords: computer-assisted composition; software model of musical form; study of musical forms; openmusic; game and education; process of composition formation; formalization of compositional method